Anti-Ma and anti-Ta associated paraneoplastic neurological syndromes: 22 newly diagnosed patients and review of previous cases. Issue 7 (25th January 2008) - Hoffmann, L A; Jarius, S; Pellkofer, H L; Schueller, M; Krumbholz, M; Koenig, F; Johannis, W; la Fougere, C; Newman, T; Vincent, A; Voltz, R
Abstract : Background: Paraneoplastic neurological syndromes (PNS) are indirect remote effects of cancer on the nervous system, often associated with the presence of specific serum antibodies. The most recently described PNS defining reactivity is anti-Ma/anti-Ta. Here we present 22 newly diagnosed patients with anti-Ma or anti-Ta reactivity, refine the associated clinical picture and review all published patients to date. Patients and methods: Patients were identified by testing for PNMA1 and PNMA2 antibodies by western blotting and indirect immunofluorescence. Clinical data were obtained either by referral of the patient or from the referring physicians. Results: Analysis of 22 new patients (14 anti-Ma, eight anti-Ta) confirmed that anti-Ta are usually found in young men with limbic encephalitis and testicular germ cell tumours who stabilise neurologically with long term survival after tumour treatment. Patients with anti-Ma were of either sex, middle-aged, presented with a range of tumours and neurological symptoms and had a limited response to treatment. Furthermore, we expanded the range of associated clinical features: (1) the peripheral nervous system may be involved; (2) an overlap with anti-Hu is possible; and (3) testicular tumour manifestation can be extragonadal or detectable only at orchiectomy. Conclusion: Refining and expanding the range of anti-Ma/anti-Ta associated neurological presentations and tumours clearly demonstrated that the distinction between anti-Ma and anti-Ta associated PNS is of high clinical relevance.